Effect of whole-body vibration on delayed onset muscular soreness, flexibility, and power - Wheeler, A. A.; Jacobson, B. H. (The Journal of Strength and Conditioning Research, 2013)
Delayed onset muscle soreness (DOMS) occurs after unaccustomed or intense bouts of exercise. The effects of DOMS peak at approximately 48 hours postexercise, and DOMS is treated, albeit not highly successfully, in a variety of ways including the use of medication and therapeutic modalities. The objective of this study was to determine the effects of whole-body vibration (WBV) on DOMS through Visual Analog Scale (VAS) measures of perceived pain/soreness and to assess the effect of WBV on flexibility and explosive power after induced DOMS. Twenty healthy college-aged participants (10 men and 10 women) volunteered for this study and were randomly assigned to the experimental or the control group. Participants completed baseline measures for VAS, hamstring and lower back flexibility, and explosive power before completing a DOMS-inducing exercise. Measures for VAS, hamstring and lower back flexibility, and explosive power were measured immediately postexercise and again immediately posttreatment. Participants reported back to the laboratory for 4 additional data collections sessions. Both the experimental and control groups yielded significant differences (p < 0.05) in pretest and posttest DOMS between baseline and pretest and posttest 1, pretest and posttest 2, and pretest and posttest 3. No significance (p > 0.05) was found within or between groups when comparing preassessments and postassessments of DOMS, flexibility, or explosive power. No differences (p > 0.05) between WBV and light exercise were found for DOMS, flexibility, and explosive power. These results suggest that WBV is equally as effective as light exercise in reducing the severity of DOMS. Thus, WBV may be used as a recovery option in addition to current treatments.